Innovation in Fifth Grade Mathematics Learning through Design Thinking Models assisted by Interactive Videos - Ni Luh Komang Sri Handayani; I Wayan Widiana; Ketut Herya Darma Utami (Universitas Pendidikan Ganesha, 2026)
The low cognitive learning outcomes of students in elementary school mathematics remain a critical issue that requires serious attention. This condition is influenced by the dominant use of conventional teaching models and the limited use of engaging learning media, resulting in low student participation and inadequate conceptual understanding. This study aims to analyze the effect of the Design Thinking model assisted by interactive videos on students’ mathematics learning outcomes. The research employed a quantitative approach with a quasi-experimental method using a nonequivalent post-test only control group design. The sample consisted of 50 students divided into an experimental group and a control group. Data were collected using a multiple-choice objective test developed based on learning indicators and were analyzed using a t-test (Welch t-test). The results of the analysis showed that the t-value was greater than the t-table value, leading to the rejection of the null hypothesis. These findings indicate that the Design Thinking model assisted by interactive videos has a significant effect on improving students’ mathematics learning outcomes. In conclusion, the integration of innovative learning models with interactive media enhances student engagement and conceptual understanding. The implication of this study highlights the importance of implementing student-centered learning models supported by engaging media to improve the effectiveness of mathematics learning.